Comparison of Subciliary Approaches in Orbito-Zygomatic Fractures: Skin Flap Versus Skin–Muscle Flap. Issue 7 (October 2015) - Ozakpinar, Hulda Rifat; Sari, Elif; Tellioglu, Ali Teoman; Sandikci, Mert Muhittin; Inozu, Emre; Seven, Ergin; Eryilmaz, Tolga; Karamursel, Sebat
Abstract : Background: Because of the complications of classical subciliary incision, some modified subciliary approaches have been described in recent literature. Objectives: The aim of this study was to compare 2 commonly used subciliary approaches according to development of postoperative complications (scar formation, and ectropion). Materials and Methods: Ninety patients were included in this retrospective study. Subciliary skin flap technique (SF group) was performed to 39 patients, while the others were operated by using skin–muscle (stepped) flap technique (SMF group). Fitzpatrick skin types, genders, ages, scar scores, and ectropion scores of the patients also were recorded. Results: The mean age of the patients was 39.3 (18–99) years, and the mean follow-up period was 2.1 (1–6) years. Fitzpatrick skin-type levels were between 2 and 4 (median = 3). No difference was found between 2 groups in terms of age, follow-up period, and Fitzpatrick skin-type levels. However, the scar values of the SMF group were significantly lower than the SF group statistically. Also, there was no significant difference between males and females in SF and SMF groups in terms of scar and ectropion formation. On the other hand, scar values were lower in SMF groups rather than SF group in males. Although ectropion values were not different between SF and SMF groups in females, ectropion values of SMF group were significantly lower than SF group in males statistically. Conclusion: Subciliary skin–muscle (stepped) flap technique can be more reliable than subciliary skin flap technique for approach to orbitozygomatic fractures.